2022
DOI: 10.1007/s00402-022-04551-w
|View full text |Cite
|
Sign up to set email alerts
|

Is new always better: comparison of the femoral neck system and the dynamic hip screw in the treatment of femoral neck fractures

Abstract: Background Hip fractures in the elderly population are common and the number of patients is rising. For young and geriatric patients with undisplaced fractures osteosynthesis is the primary type of treatment. The dynamic hip screw (DHS) is around for many years and proved its value especially in displaced fractures. Since 2018 the femoral neck system (FNS) is available as an alternative showing promising biomechanical results. The aim of this study is to evaluate clinical results of the FNS and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…However, along with the recent introduction of FNS to the market, almost half of the respondents answered that FNS was the device of choice for use in performance of internal fixation. When making a smaller incision, FNS appeared to provide biomechanical properties similar to those of sliding hip screws 8) . However, owing to its intuitive and straightforward approach, multiple screw fixation was selected as the device of choice among KHS members.…”
Section: Discussionmentioning
confidence: 96%
“…However, along with the recent introduction of FNS to the market, almost half of the respondents answered that FNS was the device of choice for use in performance of internal fixation. When making a smaller incision, FNS appeared to provide biomechanical properties similar to those of sliding hip screws 8) . However, owing to its intuitive and straightforward approach, multiple screw fixation was selected as the device of choice among KHS members.…”
Section: Discussionmentioning
confidence: 96%
“…Schuetze et al. 15 assessed the clinical outcomes of the FNS versus the DHS in treating Garden grade I–IV fractures, highlighting quicker implantation and reduced blood loss with the FNS. Stassen et al.…”
Section: Discussionmentioning
confidence: 99%
“… 29) Some studies have reported early full weight-bearing after FNS fixation, while others have reported that early ambulation before 6 weeks postoperatively is a risk factor for failure after FNS. 16 30) Our study used a sequential protocol from standing to toe-touch ambulation, gradually increasing partial weight-bearing, followed by full weight-bearing, rather than mandating full weight-bearing at a specific postoperative time point as in other studies, which may have reduced the risk of early failure of the FNS.…”
Section: Discussionmentioning
confidence: 99%